2018
DOI: 10.1111/1462-2920.14077
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and ultrastructure of meso‐ and thermophilic methanotrophic consortia

Abstract: SummaryThe sulfate‐dependent, anaerobic oxidation of methane (AOM) is an important sink for methane in marine environments. It is carried out between anaerobic methanotrophic archaea (ANME) and sulfate‐reducing bacteria (SRB) living in syntrophic partnership. In this study, we compared the genomes, gene expression patterns and ultrastructures of three phylogenetically different microbial consortia found in hydrocarbon‐rich environments under different temperature regimes: ANME‐1a/HotSeep‐1 (60°C), ANME‐1a/Seep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
173
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(194 citation statements)
references
References 81 publications
16
173
0
Order By: Relevance
“…To construct the heat map, we first downloaded the protein sequences related to the MAO pathways of ANME-1 (Hallam et al, 2003;Meyerdierks et al, 2010), ANME-2 (a/b, c, d, Wang et al, 2014;Krukenberg et al, 2018;Haroon et al, 2013), ANME-3 (Niemann et al, 2006, no genomic data), Ca. To construct the heat map, we first downloaded the protein sequences related to the MAO pathways of ANME-1 (Hallam et al, 2003;Meyerdierks et al, 2010), ANME-2 (a/b, c, d, Wang et al, 2014;Krukenberg et al, 2018;Haroon et al, 2013), ANME-3 (Niemann et al, 2006, no genomic data), Ca.…”
Section: De Novo Assembly Binning Annotation and Taxonomic Classifimentioning
confidence: 99%
See 1 more Smart Citation
“…To construct the heat map, we first downloaded the protein sequences related to the MAO pathways of ANME-1 (Hallam et al, 2003;Meyerdierks et al, 2010), ANME-2 (a/b, c, d, Wang et al, 2014;Krukenberg et al, 2018;Haroon et al, 2013), ANME-3 (Niemann et al, 2006, no genomic data), Ca. To construct the heat map, we first downloaded the protein sequences related to the MAO pathways of ANME-1 (Hallam et al, 2003;Meyerdierks et al, 2010), ANME-2 (a/b, c, d, Wang et al, 2014;Krukenberg et al, 2018;Haroon et al, 2013), ANME-3 (Niemann et al, 2006, no genomic data), Ca.…”
Section: De Novo Assembly Binning Annotation and Taxonomic Classifimentioning
confidence: 99%
“…A heat map of genes involved in reverse methanogenesis, coenzyme recycling and electron transfer, onecarbon compounds and acetyl-CoA metabolism from the current M8 metagenomic and metatranscriptomic datasets was constructed based on calculations of the average sequencing depth and FPKM values of each gene described above, with multi-subunit enzymes displayed as the average of these values for all subunits. To construct the heat map, we first downloaded the protein sequences related to the MAO pathways of ANME-1 (Hallam et al, 2003;Meyerdierks et al, 2010), ANME-2 (a/b, c, d, Wang et al, 2014;Krukenberg et al, 2018;Haroon et al, 2013), ANME-3 (Niemann et al, 2006, no genomic data), Ca. Syntrophoarchaeum spp.…”
Section: De Novo Assembly Binning Annotation and Taxonomic Classifimentioning
confidence: 99%
“…It has been shown that methane‐oxidation by ANME‐2 archaea in deep‐sea sediments can be catabolically and anabolically decoupled from sulfate‐reduction and the activity of their deltaproteobacterial partners using soluble oxidants, including anthraquinone‐2,6‐disulfonate (AQDS), humic acids and iron(III)‐citrate (Scheller et al, ), consistent with a syntrophic electron exchange between Archaea and Bacteria in the consortia (McGlynn et al, ; Wegener et al, ). Moreover, large S‐layer associated multiheme cytochromes were observed to be encoded by ANME‐2 genomes, and appear to be related to electron transfer in ANME‐2/SRB consortia as observed by transmission electron microscopy (TEM) (McGlynn et al, ; Krukenberg et al, ). TEM on thin sections of thermophilic AOM consortia further reported pili‐like structures with diameters of 10 nm and apparent lengths of 100 nm to > 1000 nm, which connect SRB HotSeep‐1 and ANME‐1 cells (Wegener et al, ), suggestive of DIET.…”
Section: Introductionmentioning
confidence: 99%
“…Methanogens such as Methanothrix (formerly Methanosaeta ) and Methanosarcina species can accept electrons via direct interspecies electron transfer from electron-donating partners, such as Geobacter species in important methanogenic environments such as anaerobic digesters and rice paddy soils (1012). Anaerobic methane oxidation also plays an important role in the global carbon cycle and diverse anaerobic methane-oxidizing archaea (ANME) transfer electrons derived from methane oxidation to extracellular electron acceptors, such as other microbial species, Fe(III), or extracellular quinones (1319). The electrical contacts for extracellular electron exchange have yet to be definitively identified in any of these Archaea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that outer-surface cytochromes enable electron transfer to electron-accepting microbial partners or Fe(III) in some ANME (1319). Genes for multi-heme c -type cytochromes that are present in ANME genomes can be highly expressed and in some instances the proteins have been detected.…”
Section: Introductionmentioning
confidence: 99%